Histiocytosis of Langerhans cells bone to polyostotic form. A case report - Jorge César Pedroso Delgado; Rafael Pila Pérez; Pedro Rosales Torres; Ivett Rivera Lecha (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
A case of a 39-year-old male patient is presented with a history of good apparent health who was admitted to the oncology clinic, due to articular pain in the costal, cervical and lumbar sacral regions that made walking difficult. In addition, It was noticed an increase in volume in the right lateral region of the forehead. Initially, he was admitted with a diagnosis of multiple myeloma and spinal cord compression to receive treatment with radiotherapy. Imaging, histo-pathological and immune-histo-chemical studies confirmed the histio-cytosis of bone langerhans to a polyostotic form.